435 Left ventricular reverse remodeling and angiotensin ii receptor blocker neprilysin inhibitor - a real-world data. (17th January 2020) - Martinho, A; Almeida, J; Freitas, A; Ferreira, C; Franco, F; Costa, S; Baptista, R; Pinho, A; Robalo, M; Goncalves, L
Abstract: BACKGROUND: Although sacubitril/valsartan (ARNI) improves the NYHA functional class and prognosis in patients with heart failure with reduced ejection fraction (HFrEF), its impact on reverse remodelling is uncertain. We assessed left ventricular reverse remodeling in a cohort of HFrEF patients treated with ARNI. METHODS: We conducted a single-centre, retrospective, observational study of 200 HFrEF patients started on ARNI during 2018. Of these, we analysed 100 patients treated with the maximum, target dose (97/103 mg bid). Baseline clinical, laboratory and demographic characteristics were evaluated and a clinical and echocardiographic follow-up, including left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (GLS), left ventricular end-systolic volume (LVESV), left ventricular end-diastolic volume (LVEDV) and mitral valve regurgitation (MR), were conducted from ARNI initiation to a 3-month landmark. RESULTS: Mean age was 59 ± 13 years and 85% were male. At baseline, 63% were on NYHA II, 34% in NYHA III and 3% in NYHA IV functional class. Mean systolic blood pressure was 125 ± 16 mmHg, median NT-proBNP was 773 pg/dL (IQR 386-1569) and mean LVEF 27 ± 7%. Median time between initiation of the drug and reaching the target dose was 10 weeks. Functional class significantly improved; at baseline, 37% of patients were in NYHA III-IV; 3 months after target dose, only 6% remained in NYHA III-IV (p = 0.005). Half of patients (48.6%) improved LVEF (from 27 ± 7% to 31 ± 10%, mean increase 4.2 ± 8.8%; 95%CI 2.1 to 6.3, p < 0.001) and in one quarter (24.6%) LVEF improved over 35% (p < 0.001). In a echocardiographic subgroup analysis, including a random sample of 35 patients, we found a significant improvement in GLS 1.5 ± 2.9 (95%CI 0.4 to 2.6%, p = 0.009), a significant decrease in LVESV and LVEDV 29 ± 3 mL (95%CI -42.6mL to -15.4mL, p < 0.001) and 31 ± 47ml (95% CI -48 to -15, p < 0.001), respectively, and a significant improvement in MR severity (p = 0.001). CONCLUSIONS: We observed that in an HFrEF patient population treated with ARNI there was a significant clinical improvement, who may be explained by a robust impact on reverse remodelling, even on a short-time of follow-up. An interesting finding was that 24.6% improved LVEF above the 35% cut-off, and therefore lost an indication for a prophylactic implantable cardioverter defibrillator.